Identification of QTLs for early maturity-related traits based on RIL population of two elite cotton cultivars - Xiaoge Wang; Fanjin Kong; Liying Gao; Guifang Shen; Bing Duan; Zongwen Wang; Dongdong Xu; Degang Fan; Yongsheng Deng; Zongfu Han (BMC Plant Biology)
Abstract Background Early-maturity cotton varieties have the potential to be cultivated in a wider geographical area, extending as far north as 46 °N in China, and confer to address the issue of competition for land between grain and cotton by reducing their whole growth period (WGP). Therefore, it is of great importance to develop cotton varieties with comprehensive early maturity and high yield following investigating the regulatory mechanism underlying early maturity and identifying early maturity-related genes. Results In this study, ‘SCRC19’ and ‘SCRC21’, two excellent cultivars with significantly different WGP, along with their recombinant inbred lines (RILs) consisting of 150 individuals were re-sequenced, yielding 4,092,677 high-quality single nucleotide polymorphisms (SNPs) and 794 bin markers across 26 chromosomes. A genetic map spanning 2213.71 cM was constructed using the 794 bin markers. Based on this map, we identified a total of 78 early maturity-related QTLs, including 12 QTLs for WGP, 4 for SSP, 12 for SFP, 3 for FBP, 11 for NFFB, 8 for NFB, 16 for HNFFB and 12 for PH. Six QTL clusters, each containing more than four traits, were identified. One particular QTL cluster, which had the largest number of QTLs, ranged from 108.5 cM to 109 cM on Dt3, and contained 39 genes. Through functional analysis, we highlighted two early maturity-related candidates of GH_D03G1554 and GH_D03G1541, which were annotated as a BEL1-like homeodomain protein 8 and a homeobox-leucine zipper family protein, respectively. Conclusions We have identified a QTL cluster related to six early maturity-associated traits on Dt3. Through annotation of genes from candidate region, we have identified two candidate genes, GH_D03G1554 and GH_D03G1541, whose expression levels in ‘SCRC21’ were significantly higher than those in ‘SCRC19’ at different stages of flower bud development. These candidate genes provide new insights into the study of early-maturity mechanism and offer potential genetic improvement of cotton.